Intrapersonal Achievement Goals and Underlying Reasons among Long Distance Runners: Their Relation with Race Experience, Self-Talk, and Running Time. Issue 3 (13th July 2016) - Delrue, Jochen; Mouratidis, Athanasios; Haerens, Leen; De Muynck, Gert-Jan; Aelterman, Nathalie; Vansteenkiste, Maarten
In a sample of long distance runners, we examined the role of type of intrapersonal achievement goals (i.e., approach versus avoidance) and type of underlying reasons (i.e., autonomous and controlled), assessed prior to the race, as predictors of both pre-race (e.g., race appraisals) and post-race (e.g., flow experience) outcomes. Of 221 (62.4% males) runners, 111 reported pursuing an intrapersonal-approach goal (i.e., doing better than before) as their dominant or preferred achievement goal for the race, while 86 prioritized intrapersonal-avoidance goals (i.e., avoiding to perform worse than before). Regression and path analyses showed that the type of achievement goals predicted none of the outcomes except for running time, with approach goals predicting better performance when compared to avoidance goals. Path analyses revealed that autonomous reasons underlying intrapersonal goal pursuit related positively to pre-race challenge appraisals, performance and, via need satisfaction, to flow experience. Interestingly, controlled reasons positively related to pre-race threat appraisals and positively predicted both positive and negative self-talk, with both yielding opposing relations with flow. These findings complement past research on the intersection between the Achievement Goal Approach and Self-Determination Theory and highlight the value of studying the reasons underlying intrapersonal achievement goals.